Processes Involved in School Improvement: Institutional Conditions for Improvement - Víctor M. Hernández Rivero; Pablo Santana Bonilla (Universidad Autónoma de Madrid, 2016)
School effectiveness and school improvement research results have shown that certain conditions must be present for improvement processes to be developed. Ainscow et al. have identified six of such conditions. Those conditions are, in fact, processes usually present after and during the development of improvement efforts. In order to explore the presence or lack of those processes we asked teachers from 45 schools participating in a programme of school evaluation to complete Aisncow et al. (2001) scale on institutional conditions for improvement. We also gathered information about the improvement plans developed by the schools.The schools analyzed were very different but there were four of them that presented the six conditions. Coordination of activities and communication, and enquiry and reflection were the two conditions more cited by teachers as present in their schools. The encouragement of involvement and the availability of staff development opportunities were the conditions more cited by teachers as absent in their schools. Distributed school leadership revealed as a key condition because it is present in schools with four or more conditions. In conclusion, the six internal conditions for improvement could be part of an inventory of processes involved in educational institutions improvement, although some of them appear more than others in the schools sample analyzed.